Photonuclear production of Pm-149 - Dikiy, N.P.; Dovbnya, A.N.; Lyashko, Yu.V.; Medvedeva, E.P.; Medvedev, D.V.; Uvarov, V.L. (Вопросы атомной науки и техники, 2015)
¹⁵³Sm is successfully used for palliative treatment of patients with bone metastases and pain. ¹⁵³Sm is being produced in the reactors by means of irradiating of ¹⁵²Sm. In radio-labelled radiopharmaceuticals per each isotope of ¹⁵³Sm contained about 1000 atoms of the ¹⁵²Sm, which greatly influence the kinetics of its transport into the tumor. Production of ¹⁴⁹Pm isotopes that do not contain impurities of other isotopes, it was implemented using photonuclear reactions. The characteristics ¹⁴⁹Pm is practically coincides with the parameters of ¹⁵³Sm. The irradiation of neodymium of natural isotopic composition was carried out by means of bremsstrahlung with a maximum energy of 12.5 MeV. For production of ¹⁴⁹Рm the reaction ¹⁵⁰Nd(γ,n)¹⁴⁹Nd (T1/2=1.73 hours) → ¹⁴⁹Pm was used. Reaction ¹⁴⁸Nd(γ,n)¹⁴⁷Nd (T1/2=10.93 days) → ¹⁴⁷Pm (T1/2=2.62 years) will lead to low activity ¹⁴⁷Pm provided daily extraction ¹⁴⁹Pm. The rare earth elements of cerium group successfully are separated in a multistage extraction column using a normal tributyl ester of phosphoric acid. Для паліативної терапії хворих з метастазами в кістках і болісному синдромі успішно використовується ¹⁵³Sm, що виробляється на реакторах при опроміненні ізотопу ¹⁵²Sm. У радіопрепараті, який використовується, на кожен ізотоп ¹⁵³Sm приходиться близько 1000 атомів ізотопу ¹⁵²Sm, що істотно впливає на кінетику його надходження в пухлину. Виробництво ізотопів, що не містять домішок інших ізотопів, передбачається реалізувати з використанням фотоядерного виробництва ¹⁴⁹Рm, що за своїми характеристиками практично збігається з параметрами ¹⁵³Sm. Проведено опромінення неодиму природного ізотопного складу гальмівним випромінюванням з максимальною енергією 12,5 МеВ. Для виробництва ¹⁴⁹Рm використовувалася реакція ¹⁵⁰Nd(γ,n)¹⁴⁹Nd (Т1/2=1,73 год.) → ¹⁴⁹Рm. Реакція 148Nd(γ,n)¹⁴⁷Nd (Т1/2=10,93 дня) → ¹⁴⁷Рm (Т1/2=2,62 роки) буде утворювати малу активность ¹⁴⁷Рm за умови щоденного виділення ¹⁴⁹Рm. Рідкоземельні елементи церієвої групи успішно розділяються в багатоступінчастих екстракціонних колонах з використанням нормального трибутилового ефіру ортофосфорної кислоти. Для паллиативной терапии больных с метастазами в кости и болевым синдромом успешно используется ¹⁵³Sm, который производится на реакторах при облучении изотопа ¹⁵²Sm. В используемом радиопрепарате на каждый изотоп ¹⁵³Sm приходится около 1000 атомов изотопа ¹⁵²Sm, что существенно влияет на кинетику его поступления в опухоль. Производство изотопов, не содержащих примесей других изотопов, предполагается реализовать при помощи фотоядерного производства ¹⁴⁹Рm, который по своим характеристикам практически совпадает с параметрами ¹⁵³Sm. Проведено облучение неодима естественного изотопного состава тормозным излучением с максимальной энергией 12,5 МэВ. Для производства ¹⁴⁹Рm использовалась реакция ¹⁵⁰Nd(γ,n)¹⁴⁹Nd (Т1/2=1,73 часа) → ¹⁴⁹Рm. Реакция ¹⁴⁸Nd(γ,n)¹⁴⁷Nd (Т1/2=10,93 дня) → ¹⁴⁷Рm (Т1/2=2,62 года) будет создавать малую активность ¹⁴⁷Рm при условии ежедневного выделения ¹⁴⁹Рm. Редкоземельные элементы цериевой группы успешно разделяются в многоступенчатых экстракционных колоннах с использованием нормального трибутилового эфира ортофосфорной кислоты.